Catalyst, preparation method and application thereof
By using urea, polyethylene glycol, boric acid and nickel nitrate at high temperature, a low-cost catalyst was prepared, which solved the problem of high preparation cost of precious metal catalysts and improved the discharge performance of the battery.
Patent Information
- Application Number
- CN202510110864.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-01-23
AI Technical Summary
The existing precious metal catalysts are costly to be prepared and difficult to effectively reduce, which affects the discharge performance and range of the battery.
Urea, polyethylene glycol, boric acid and nickel nitrate are used as reaction raw materials and fired at high temperatures to prepare a low-cost catalyst.
The production cost of the catalyst is reduced and the discharge performance of the battery is improved by catalyzing the conversion of 5-hydroxymethylfurfural to 2,5-furandicarboxylic acid.
Smart Images

Figure CN119920915A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a catalyst, a preparation method and application thereof. Background Art
[0002] With the development of new energy vehicles, the discharge performance of batteries directly affects the battery life, and thus the vehicle's range. Among them, 2,5-furandicarboxylic acid (FDCA) can enhance the discharge performance of batteries, and FDCA can be obtained by catalytic oxidation of 5-hydroxymethylfurfural (HMF) under the action of a catalyst. Therefore, it is very important to prepare a catalyst that can catalyze the conversion of HMF into FDCA.
[0003] The catalysts in the related art are mainly precious metal catalysts, such as platinum, gold and their alloys, but the preparation cost of precious metal catalysts is relatively high. Summary of the invention
[0004] The embodiments of the present application provide a catalyst, a preparation method and an application thereof, which can reduce the preparation cost of the catalyst. The technical solution is as follows:
[0005] In one aspect, a method for preparing a catalyst is provided, the method comprising:
[0006] Mixing urea, polyethylene glycol, boric acid and nickel nitrate uniformly to obtain a mixture;
[0007] The mixture is placed in a crucible and fired in a tube furnace filled with argon atmosphere; wherein the firing temperature is 690-710° C. and the firing time is 130-140 min;
[0008] After reaching the sintering time, the catalyst is obtained by keeping the temperature for 235 to 245 minutes.
[0009] In a possible implementation, the mass fraction of urea is 11 parts, the mass fraction of polyethylene glycol is 1 part, the mass fraction of boric acid is 0.3 parts, and the mass fraction of nickel nitrate is 5 to 250 parts.
[0010] In another possible implementation, the urea, polyethylene glycol, boric acid and nickel nitrate are uniformly mixed to obtain a mixture, comprising:
[0011] Grinding urea solid, polyethylene glycol solid, boric acid solid and nickel nitrate solid into powders respectively to obtain urea powder, polyethylene glycol powder, boric acid powder and nickel nitrate powder;
[0012] The urea powder, the polyethylene glycol powder, the boric acid powder and the nickel nitrate powder are uniformly mixed to obtain the mixture.
[0013] In another possible implementation, the urea, polyethylene glycol, boric acid and nickel nitrate are uniformly mixed to obtain a mixture, comprising:
[0014] Evenly mixing urea solid, polyethylene glycol solid, boric acid solid and nickel nitrate solid to obtain a mixed solid;
[0015] The mixed solids are ground into powder to obtain the mixture.
[0016] In another possible implementation, after reaching the firing time, the catalyst is obtained by keeping the temperature for 235 to 245 minutes, comprising:
[0017] After reaching the firing time, the temperature is kept at 235 to 245 minutes, and then the temperature is lowered to room temperature to obtain a catalyst to be cleaned;
[0018] The catalyst to be cleaned is washed multiple times with ultrapure water, the washed catalyst is placed in a vacuum drying oven, dried at 38-42° C., and taken out after 24 hours to obtain the catalyst.
[0019] In another possible implementation, the firing temperature is 700°C.
[0020] In another possible implementation, the firing time is 135 minutes.
[0021] In another possible implementation, the molecular weight of the polyethylene glycol is 2000.
[0022] On the other hand, a catalyst is provided, wherein the catalyst is prepared by any of the preparation methods described above.
[0023] On the other hand, provided is a use of a catalyst prepared by any of the preparation methods described above in catalyzing the conversion of 5-hydroxymethylfurfural into 2,5-furandicarboxylic acid.
[0024] The present application provides a catalyst, which uses urea, polyethylene glycol, boric acid and nickel nitrate as reaction raw materials. Compared with precious metal catalysts, these reaction raw materials are cheap and easy to obtain, so the preparation cost of the catalyst can be reduced. In addition, the catalyst can be obtained by calcining the above reaction raw materials at high temperature in a tube furnace. It can be seen that the preparation method of the catalyst is simple and easy to operate.
[0025] It should be understood that the foregoing general description and the following detailed description are exemplary only and are not restrictive of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 is a flow chart of a method for preparing a catalyst provided in an embodiment of the present application;
[0028] Figure 2 This is a schematic diagram of the conversion of HMF into FDCA provided in an embodiment of the present application;
[0029] Figure 3 is a schematic diagram of an LSV curve provided in an embodiment of the present application;
[0030] Figure 4 It is a schematic diagram of an LSV curve provided in an embodiment of the present application. DETAILED DESCRIPTION
[0031] The technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.
[0032] At present, there are mainly the following methods for converting HMF into FDCA:
[0033] The first method is direct oxidation. HMF is oxidized to FDCA using a strong oxidizing agent. For example, the oxidizing agent is hydrogen peroxide. However, this method will generate by-products, and the purity of the generated FDCA is low, which will increase the subsequent separation cost.
[0034] The second method is biocatalysis, which uses enzyme catalysis or whole-cell catalysis to promote the reaction. It is usually carried out in a relatively mild environment and can catalyze waste into useful renewable resources, which is very consistent with the current concept of green environmental protection.
[0035] The third method is electrocatalysis. The electrocatalysis method is driven by an external potential, so there is no need to add strong oxidants and enzymes to catalyze the conversion of HMF to FDCA. The electrocatalysis method has multiple significant advantages such as green environmental protection, high controllability, and reaction conditions and temperature. It is a highly anticipated technical approach. Its green and environmentally friendly characteristics can reduce the generation of harmful substances during the catalytic process, which is of great significance for environmental protection.
[0036] The catalyst prepared in this application is to catalyze the conversion of HMF into FDCA by electrocatalysis. The preparation method of the catalyst provided in this application is introduced below.
[0037] The present invention provides a method for preparing a catalyst. Figure 1 , the preparation method comprises:
[0038] Step 101: Evenly mix urea, polyethylene glycol, boric acid and nickel nitrate to obtain a mixture.
[0039] This step can be achieved in any of the following ways.
[0040] The first implementation method is to grind urea solid, polyethylene glycol solid, boric acid solid and nickel nitrate solid into powders respectively to obtain urea powder, polyethylene glycol powder, boric acid powder and nickel nitrate powder; and mix the urea powder, polyethylene glycol powder, boric acid powder and nickel nitrate powder evenly to obtain a mixture.
[0041] The second implementation method is to uniformly mix urea solid, polyethylene glycol, boric acid solid and nickel nitrate solid to obtain a mixed solid; and grind the mixed solid into powder to obtain a mixture.
[0042] In the embodiment of the present application, the mass fraction of urea is 11 parts, the mass fraction of polyethylene glycol is 1 part, the mass fraction of boric acid is 0.3 parts, and the mass fraction of nickel nitrate is 5 to 250 parts.
[0043] Among them, the mass parts of nickel nitrate can be 5 parts, 10 parts, 20 parts, 30 parts, 60 parts, 80 parts, 100 parts, 120 parts, 150 parts, 180 parts, 200 parts, 220 parts, and 250 parts.
[0044] The molecular weight of the polyethylene glycol can be selected as needed and is not specifically limited thereto. For example, the molecular weight of the polyethylene glycol is 2000 or 4000. In the embodiments of the present application, only the molecular weight of the polyethylene glycol is 2000 as an example for illustration.
[0045] One thing that needs to be explained is that before this step, urea solid, polyethylene glycol solid, boric acid solid and nickel nitrate solid can be placed in a container respectively, and then a certain volume of ultrapure water is added to each of them, washed with ultrapure water, and then placed in a blast drying oven to dry. After drying, step 101 is performed.
[0046] The volume of ultrapure water can be set and changed as needed, and is not specifically limited thereto. For example, the volume of ultrapure water is 50 mL.
[0047] The temperature of the blast drying oven can be set and changed as needed, and is not specifically limited thereto. For example, the temperature of the blast drying oven is 80°C.
[0048] The drying time can also be set and changed as needed, and is not specifically limited to this. For example, the drying time is 24 hours.
[0049] Step 102: The mixture is placed in a crucible and fired in a tube furnace filled with argon atmosphere.
[0050] The mixture is placed in a crucible and fired in a tubular furnace filled with argon at a temperature of 690 to 710° C. for 130 to 140 minutes.
[0051] The firing temperature may be 690°C, 695°C, 700°C, 705°C, 710°C, and the firing time may be 130min, 132min, 135min, 138min, 140min. In the embodiment of the present application, only the firing temperature of 700°C and the firing time of 135min are used as an example for explanation.
[0052] In the embodiment of the present application, urea, polyethylene glycol, boric acid and nickel nitrate react at high temperature to generate a catalyst, which can be represented by Ni / BNC. Among them, if the firing temperature is too high or too low, or the firing time is too long or too short, the catalyst provided by the present application cannot be generated.
[0053] Step 103: After the firing time is reached, keep the temperature for 235 to 245 minutes to obtain the catalyst.
[0054] After the firing time is reached, the temperature is kept for 235 to 245 minutes, and the temperature is lowered to room temperature to obtain the catalyst to be cleaned; the catalyst to be cleaned is washed multiple times with ultrapure water, and the washed catalyst is placed in a vacuum drying oven, dried at 38 to 42°C, and taken out after 24 hours to obtain the catalyst.
[0055] Among them, the insulation time can be 235min, 238min, 240min, 242min, and 245min. In the embodiment of the present application, only the insulation time of 240min is taken as an example for illustration.
[0056] The drying temperature of the vacuum drying oven can be 38°C, 39°C, 40°C, 41°C, or 42°C. In the embodiment of the present application, only the drying temperature of 40°C is used as an example for illustration.
[0057] The number of washing times can be set and changed as needed, and is not specifically limited to this. For example, the number of washing times is 3 times, 4 times or 5 times.
[0058] In the examples of the present application, after obtaining the catalyst, the catalyst can be placed in a sample bottle and taken out when waiting for subsequent use.
[0059] The present application provides a catalyst, which uses urea, polyethylene glycol, boric acid and nickel nitrate as reaction raw materials. Compared with precious metal catalysts, these reaction raw materials are cheap and easy to obtain, so the preparation cost of the catalyst can be reduced. In addition, the catalyst can be obtained by calcining the above reaction raw materials at high temperature in a tube furnace. It can be seen that the preparation method of the catalyst is simple and easy to operate.
[0060] On the other hand, an embodiment of the present application provides a catalyst, which is prepared using the above-mentioned preparation method.
[0061] On the other hand, an embodiment of the present application provides a use of a catalyst in catalyzing the conversion of HMF into FDCA.
[0062] It should be noted that there are two main pathways for HMF to be converted into FDCA. The first is HMF→DFF→FFCA→FDCA, and the second is HMF→HMFCA→FFCA→FDCA, see Figure 2 The catalyst prepared in the present application mainly catalyzes the conversion of HMF into FDCA through the second pathway, that is, HMF is first converted into HMFCA, then into FFCA, and finally into FDCA under the catalytic action of the catalyst.
[0063] The exemplary embodiments of the present application will be described in more detail below. Although the exemplary embodiments of the present application are described below, it should be understood that the present application can be implemented in various forms and should not be limited by the embodiments set forth herein.
[0064] If no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in the field or the product instructions are used. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0065] Example 1
[0066] Step 1: Weigh 11 g of urea, 1 g of PEG-2000 (polyethylene glycol), 0.3 g of boric acid and 15 mg of nickel nitrate, mix them evenly, and then grind them into powder to obtain a mixture.
[0067] Step 2: The mixture is placed in a crucible and fired in a tube furnace filled with argon atmosphere at a temperature of 700° C. for 135 min.
[0068] Step 3: After reaching the firing time, keep warm for 240 minutes, cool to room temperature, and obtain the catalyst to be cleaned; wash the catalyst to be cleaned with ultrapure water for multiple times, put the washed catalyst into a vacuum drying oven, dry it at 40°C, take it out after 24 hours, and obtain the catalyst, which is marked as Ni / BNC-15mg.
[0069] Example 2
[0070] Step 1: Weigh 11 g of urea, 1 g of PEG-2000 (polyethylene glycol), 0.3 g of boric acid and 30 mg of nickel nitrate, mix them evenly, and then grind them into powder to obtain a mixture.
[0071] Step 2: The mixture is placed in a crucible and fired in a tube furnace filled with argon atmosphere at a temperature of 700° C. for 135 min.
[0072] Step 3: After reaching the firing time, keep warm for 240 minutes, cool to room temperature, and obtain the catalyst to be cleaned; use ultrapure water to wash the catalyst to be cleaned for multiple times, put the washed catalyst into a vacuum drying oven, dry it at 40°C, take it out after 24 hours, and obtain the catalyst, which is marked as Ni / BNC-30mg.
[0073] Example 3
[0074] Step 1: Weigh 11 g of urea, 1 g of PEG-2000 (polyethylene glycol), 0.3 g of boric acid and 60 mg of nickel nitrate, mix them evenly, and then grind them into powder to obtain a mixture.
[0075] Step 2: The mixture is placed in a crucible and fired in a tube furnace filled with argon atmosphere at a temperature of 700° C. for 135 min.
[0076] Step 3: After reaching the firing time, keep warm for 240 minutes, cool to room temperature, and obtain the catalyst to be cleaned; use ultrapure water to wash the catalyst to be cleaned for multiple times, put the washed catalyst into a vacuum drying oven, dry it at 40°C, take it out after 24 hours, and obtain the catalyst, which is marked as Ni / BNC-60mg.
[0077] Example 4
[0078] Step 1: Weigh 11 g of urea, 1 g of PEG-2000 (polyethylene glycol), 0.3 g of boric acid and 120 mg of nickel nitrate, mix them evenly, and then grind them into powder to obtain a mixture.
[0079] Step 2: The mixture is placed in a crucible and fired in a tube furnace filled with argon atmosphere at a temperature of 700° C. for 135 min.
[0080] Step 3: After reaching the firing time, keep warm for 240 minutes, cool to room temperature, and obtain the catalyst to be cleaned; use ultrapure water to wash the catalyst to be cleaned for multiple times, put the washed catalyst into a vacuum drying oven, dry it at 40°C, take it out after 24 hours, and obtain the catalyst, which is marked as Ni / BNC-120mg.
[0081] In Examples 1 to 4 of the present application, nickel nitrate, polyethylene glycol, boric acid and urea are used as precursors to prepare catalysts. The mass fractions of urea, polyethylene glycol and boric acid are fixed by the controlled variable method, the mass fractions of nickel nitrate are changed, and the nickel nitrate is loaded on carbon paper to explore its effect on the electrocatalytic oxidation of HMF to generate FDCA, and then the discharge performance of the battery is tested.
[0082] Test Example 1
[0083] Take 5 mg of the catalyst respectively, add 960 μL of isopropanol solution and 40 μL of Nafion solution (perfluorosulfonic acid polymer solution) thereto, and perform ultrasonic cleaning with an ultrasonic cleaner. The ultrasonic time is 30 minutes and the water temperature is less than 30°C to achieve a uniform dispersion effect.
[0084] Use a pipette to transfer 50 μL of the catalyst solution and evenly apply the catalyst solution on the surface of 1.5 cm × 1.5 cm carbon paper, leaving an area of 1.5 cm × 1 cm for easy clamping. Then place it at room temperature and dry it for about 45 minutes to obtain a positive electrode that meets the research requirements.
[0085] Taking the catalyst prepared in Example 2 as an example, after the positive electrode is prepared according to the above method, the positive electrode is immersed in a 1 mol / L KOH solution, and the platinum sheet as the negative electrode is immersed in a 1 mol / L KOH solution. A linearly changing potential is applied to the working electrode by linear sweep voltammetry (LSV), and the corresponding current change is monitored and recorded in real time, thereby generating a current-potential curve, which is: Figure 3 The corresponding curve of KOH.
[0086] The positive electrode was immersed in a 5mmol / L HMF solution, and the platinum sheet was immersed in a 1mol / L KOH solution as the negative electrode. A linearly changing potential was applied to the working electrode by linear sweep voltammetry (LSV), and the corresponding current changes were monitored and recorded in real time to generate a current-potential curve. The curve is Figure 3 The curve 3 corresponds to HMF.
[0087] By analyzing this curve, the starting potential can be determined (the starting potential is the value of the intersection of the tangent of the LSV curve and the x-axis). The starting potential directly reflects the thermodynamic barrier faced by the catalyst during the HMF oxidation process. A lower starting potential means that the catalyst can more easily overcome the energy barrier required for the reaction, thereby exhibiting stronger discharge performance.
[0088] from Figure 3 It can be seen that when HMF solution is used, the onset potential of Ni / BNC moves significantly to the negative direction, which means that the HMF oxidation reaction is thermodynamically more favorable than the water oxidation reaction.
[0089] For the catalysts prepared in Examples 1 to 3, after the positive electrodes were prepared respectively according to the above method, the positive electrodes were immersed in a 5 mmol / L HMF solution, and the platinum sheet as the negative electrode was immersed in a 1 mol / L KOH solution, and the performance of the catalyst in catalyzing the HMF oxidation reaction was tested by linear sweep voltammetry (LSV).
[0090] See also Figure 4 , Figure 4 is the LSV curve measured based on the catalyst prepared in Examples 1 to 4, from Figure 4 It can be seen that the starting potentials of Ni / BNC-15mg, Ni / BNC-30mg, Ni / BNC-60mg and Ni / BNC-120mg all moved significantly in the negative direction. Among them, the slope of the curve corresponding to Ni / BNC-120mg is the smallest and the slope is the gentlest. Therefore, its starting potential is the lowest, indicating that its discharge performance is the strongest.
[0091] Test Example 2
[0092] The samples were quantitatively analyzed by high performance liquid chromatography (HPLC) to compare the effects of various catalysts on the electrocatalytic oxidation of HMF to produce FDCA. Before and after the electrocatalytic reaction, 10 μL of the electrolyte containing reactants and products was extracted and detected by high performance liquid chromatography. The yield of FDCA can be expressed by the following formula:
[0093]
[0094] According to the corresponding data, it can be calculated that the FDCA yields corresponding to Ni / BNC-15mg, Ni / BNC-30mg, Ni / BNC-60mg and Ni / BNC-120mg are 0.1%, 1.91%, 1.68% and 3.01% respectively. It can be seen that the FDCA yield corresponding to Ni / BNC-120mg is the highest, indicating that its discharge performance is the strongest, which is the same as the conclusion drawn in Test Example 1.
[0095] In summary, the catalyst prepared in the present application using nickel nitrate, polyethylene glycol, boric acid and urea as precursors can indeed catalyze the conversion of HMF into FDCA, thereby enhancing the discharge performance of the battery. In addition, the catalyst prepared in the present application has low cost, and the preparation method is simple and easy to operate.
[0096] The above description is only for the purpose of facilitating those skilled in the art to understand the technical solution of the present application and is not intended to limit the present application. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A method for preparing a catalyst, characterized in that: The preparation method comprises: Mixing urea, polyethylene glycol, boric acid and nickel nitrate uniformly to obtain a mixture; The mixture is placed in a crucible and fired in a tube furnace filled with argon atmosphere; wherein the firing temperature is 690-710° C. and the firing time is 130-140 min; After reaching the sintering time, the catalyst is obtained by keeping the temperature for 235 to 245 minutes.
2. The preparation method according to claim 1, characterized in that: The mass fraction of the urea is 11 parts, the mass fraction of the polyethylene glycol is 1 part, the mass fraction of the boric acid is 0.3 parts, and the mass fraction of the nickel nitrate is 5 to 250 parts.
3. The preparation method according to claim 1, characterized in that: The urea, polyethylene glycol, boric acid and nickel nitrate are uniformly mixed to obtain a mixture, comprising: Grinding urea solid, polyethylene glycol solid, boric acid solid and nickel nitrate solid into powders respectively to obtain urea powder, polyethylene glycol powder, boric acid powder and nickel nitrate powder; The urea powder, the polyethylene glycol powder, the boric acid powder and the nickel nitrate powder are uniformly mixed to obtain the mixture.
4. The preparation method according to claim 1, characterized in that: The urea, polyethylene glycol, boric acid and nickel nitrate are uniformly mixed to obtain a mixture, comprising: Evenly mixing urea solid, polyethylene glycol solid, boric acid solid and nickel nitrate solid to obtain a mixed solid; The mixed solids are ground into powder to obtain the mixture.
5. The preparation method according to claim 1, characterized in that: After reaching the firing time, the temperature is kept for 235 to 245 minutes to obtain a catalyst, comprising: After reaching the firing time, the temperature is kept at 235 to 245 minutes, and then the temperature is lowered to room temperature to obtain a catalyst to be cleaned; The catalyst to be cleaned is washed multiple times with ultrapure water, the washed catalyst is placed in a vacuum drying oven, dried at 38-42° C., and taken out after 24 hours to obtain the catalyst.
6. The preparation method according to claim 1, characterized in that: The firing temperature is 700°C.
7. The preparation method according to claim 1, characterized in that: The firing time is 135 min.
8. The preparation method according to claim 1, characterized in that: The molecular weight of the polyethylene glycol is 2000.
9. A catalyst, characterized in that The catalyst is prepared by the preparation method according to any one of claims 1 to 8.
10. Use of a catalyst prepared by the preparation method according to any one of claims 1 to 8 in catalyzing the conversion of 5-hydroxymethylfurfural into 2,5-furandicarboxylic acid.
Citation Information
Patent Citations
Method for preparing furan-2,5-dicarboxylicacid from 5-hydroxymethylfurfural through electrochemical oxidation
CN110106514A
Preparation method and application of monolithic cobalt-doped nickel-molybdenum nanowire catalyst
CN115261895A
Preparation method of nitrogen and fluorine co-doped nickel oxide micron flower balls
CN115771917A
Composite material with heterostructure as well as preparation method and application of composite material
CN116078412A
Method for preparing 2, 5-furandicarboxylic acid through electrochemical oxidation of 5-hydroxymethylfurfural
CN117660993A